2013
DOI: 10.3171/2012.11.spine12224
|View full text |Cite
|
Sign up to set email alerts
|

Revision lumbar surgery in elderly patients with symptomatic pseudarthrosis, adjacent-segment disease, or same-level recurrent stenosis. Part 1. Two-year outcomes and clinical efficacy

Abstract: Object Same-level recurrent lumbar stenosis, pseudarthrosis, and adjacent-segment disease (ASD) are potential complications that can occur after index lumbar spine surgery, leading to significant discomfort and radicular pain. While numerous studies have demonstrated excellent results following index lumbar spine surgery in elderly patients (age > 65 years), the effectiveness of revision lumbar surgery in this cohort remains unclear. The aim of this study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
3
30
0
6
Order By: Relevance
“…[18][19][20] In a recent study about revision lumbar surgery in elderly patients (age >65 years) with symptomatic pseudarthrosis, ASP, or same-level recurrent stenosis, VAS values for back pain and two-year ODI showed significant improvements two years after surgery. 21 However, informal outcome measures taking into account pain, medication use, and return to work showed a good outcome in 35.7% of cases. 20 Two years postoperatively, only 38% and 40% of patients reached the minimum clini-cally important difference (MCID) threshold for the ODI and the 36-item short-form health survey (SF-36) physical component scale, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20] In a recent study about revision lumbar surgery in elderly patients (age >65 years) with symptomatic pseudarthrosis, ASP, or same-level recurrent stenosis, VAS values for back pain and two-year ODI showed significant improvements two years after surgery. 21 However, informal outcome measures taking into account pain, medication use, and return to work showed a good outcome in 35.7% of cases. 20 Two years postoperatively, only 38% and 40% of patients reached the minimum clini-cally important difference (MCID) threshold for the ODI and the 36-item short-form health survey (SF-36) physical component scale, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Although not directly relevant to the present study because they address revision surgery, Adogwa et al 17,18 reported the results of revision decompression and arthrodesis surgery in patients with lumbar pseudarthrosis (n = 17), adjacent-level disease (n = 28), and same-level recurrent stenosis (n = 24) who were at least sixty-five years of age. The authors found that patients who underwent such surgery for those disorders had significant improvement from baseline in the ODI score and the VAS (visual analog scale) score for back pain at two years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Rare studies report good results regarding back pain, leg pain, and disability for decompression and fusion for same-level recurrent stenosis. 22,23 However, to our knowledge there are no data on re-decompression for recurrent stenosis.…”
Section: Discussionmentioning
confidence: 99%